Pressure effect on magnetic properties of valence fluctuating system Ce(Ni1-xCux)5: Электронные свойства многокомпонентных соединений - Grechnev, G.E.; Logosha, A.V.; Panfilov, A.S.; Svechkarev, I.V.; Musil, O.; Svoboda, P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Magnetic susceptibility χ of the isostructural Ce(Ni1–xCux)5 alloys (0 ≤ x ≤ 0.9) was studied as a function ofthe hydrostatic pressure up to 2 kbar at fixed temperatures 77.3 and 300 K. A pronounced pressure effect on susceptibility is found to be negative in sign and nonmonotonously dependent on the Cu content, showing a sharpmaximum at x ≃ 0.4. The experimental results are discussed in terms of the valence instability of Ce ion in the studied alloys. For the reference CeNi5 compound the main contributions to χ and their volume dependence are calculated ab initio within the local spin density approximation, and appeared to be in close agreement with experimentaldata.